BAHASA ARTIFISIAL SEBAGAI SALAH SATU WUJUD RAGAM DAN KREATIVITAS BERBAHASA - Sujarno Sujarno (Buana Bastra, 2015)
Abstract Any language that exist in the world is definitely having the same characteristics. Among these characteristics are arbitrary, creative, and dynamic. As the manifestations known there are common language and arificial language. Common language is also know by the name of natural language, colloquial, or non cognitive language. Artificial language is synonimous with scientific language, the language of science, and cognitive language. Common language is characterized by emotional, evaluative, ambiguous, and prejudiced/contextual. Otherwise artificial language, closed to the facts, meaningful constant, single definition, and non personal. Key Word: Artificial language, common language, arbitrary, creative, dynamic.